Brain iron overload following intracranial haemorrhage. Issue 4 (29th November 2016) - Garton, Thomas; Keep, Richard F; Hua, Ya; Xi, Guohua
Abstract : Intracranial haemorrhages, including intracerebral haemorrhage (ICH), intraventricular haemorrhage (IVH) and subarachnoid haemorrhage (SAH), are leading causes of morbidity and mortality worldwide. In addition, haemorrhage contributes to tissue damage in traumatic brain injury (TBI). To date, efforts to treat the long-term consequences of cerebral haemorrhage have been unsatisfactory. Incident rates and mortality have not showed significant improvement in recent years. In terms of secondary damage following haemorrhage, it is becoming increasingly apparent that blood components are of integral importance, with haemoglobin-derived iron playing a major role. However, the damage caused by iron is complex and varied, and therefore, increased investigation into the mechanisms by which iron causes brain injury is required. As ICH, IVH, SAH and TBI are related, this review will discuss the role of iron in each, so that similarities in injury pathologies can be more easily identified. It summarises important components of normal brain iron homeostasis and analyses the existing evidence on iron-related brain injury mechanisms. It further discusses treatment options of particular promise.